The Effect of the BC-MK15 Birth Chair on the Labor Pain Intensity in Multipara - Yetti Purnama; Johanes Cornelius Mose; Herry Herman (Universitas Islam Bandung, 2018)
Labor pain causes worry, anxiety, increases the secretion of the adrenaline, adrenocorticotropic hormone (ACTH), cortisol serum levels, catecholamines and the perception of pain. One method to decrease labor pain is through the mobilization and upright position during labor which is facilitated by the BC-MK15 birth chair to relax, decrease catecholamines, increase the release of β-endorphins and block the transmission of pain stimulus. This study aims was analyze the difference of the effect of using the BC-MK15 birth chair and the conventional bed on the intensity of labor pain in multipara. The design of this study was the posttest-only control group design in 60 samples of the first active phase of multipara at Public Health Centers Garuda, Ibrahim Adjie and Puter of Bandung city in April–May 2017. Each group consisted of 30 for treatment (using BC-MK15 birth chair) and control (using the conventional bed). Assessment of pain scores using the visual analogue scale (VAS) in cervical dilations of 4 cm (post 1), 7–9 cm (post 2) and 10 cm (post 3). The statistical test analysis uses the Mann-Whitney test and the chi-square test. There were significant differences among groups which are obtained by the treatment and control of post 2 and post 3 (p<0.05, RR=0.69 [0.531–0.896]). In conclusion, there is an effect of using the BC-MK15 birth chair and the conventional bed on the intensity of labor pain in multiparous mothers. PENGARUH KURSI PERSALINAN BC-MK15 TERHADAP INTENSITAS NYERI PERSALINAN PADA MULTIPARANyeri persalinan menimbulkan rasa khawatir, kecemasan, meningkatkan sekresi adrenalin, adrenocorticotropic hormone (ACTH), kadar kortisol serum, katekolamin, dan persepsi nyeri. Salah satu metode menurunkan nyeri persalinan adalah mobilisasi dan posisi tegak saat persalinan difasilitasi dengan kursi persalinan BC-MK15 sehingga menimbulkan relaksasi, menurunkan katekolamin, meningkatkan pelepasan β-endorfin, dan mengeblok transmisi stimulus nyeri. Penelitian ini bertujuan menganalisis perbedaan pengaruh penggunaan kursi persalinan BC-MK15 dan tempat tidur konvensional terhadap intensitas nyeri persalinan pada multipara. Desain penelitian eksperimen posttest-only control group design dengan jumlah sampel 60 multipara kala I fase aktif di Puskesmas Garuda, Ibrahim Adjie, dan Puter Kota Bandung pada bulan April–Mei 2017. Tiap-tiap kelompok berjumlah 30 untuk perlakuan (menggunakan kursi persalinan BC-MK15) dan kontrol (menggunakan tempat tidur konvensional). Penilaian skor nyeri menggunakan visual analogue scale (VAS) pada dilatasi serviks 4 cm (post 1), 7–9 cm (post 2), dan 10 cm (post 3). Pengujian statistik menggunakan analisis Uji Mann-Whitney dan uji chi-square. Didapatkan perbedaan bermakna antara kelompok perlakuan dan kontrol pada post 2 dan post 3 (p<0,05; RR=0,69 [0,531–0,896]). Simpulan, terdapat pengaruh penggunaan kursi persalinan BC-MK15 dan tempat tidur konvensional terhadap intensitas nyeri persalinan pada ibu multipara.